Defective glycinergic synaptic transmission in zebrafish motility mutants - Hirata, Hiromi; Carta, Eloisa; Yamanaka, Iori; Harvey, Robert J.; Kuwada, John Y. (Frontiers in Molecular Neuroscience, 2010)
Glycine is a major inhibitory neurotransmitter in the spinal cord and brainstem. Recently, in vivo analysis of glycinergic synaptic transmission has been pursued in zebrafish using molecular genetics. An ENU mutagenesis screen identified two behavioral mutants that are defective in glycinergic synaptic transmission. Zebrafish bandoneon (beo) mutants have a defect in glrbb, one of the duplicated glycine receptor (GlyR) β subunit genes. These mutants exhibit a loss of glycinergic synaptic transmission due to a lack of synaptic aggregation of GlyRs. Due to the consequent loss of reciprocal inhibition of motor circuits between the two sides of the spinal cord, motor neurons activate simultaneously on both sides resulting in bilateral contraction of axial muscles of beo mutants, eliciting the so-called ‘accordion’ phenotype. Similar defects in GlyR subunit genes have been observed in several mammals and are the basis for human hyperekplexia/startle disease. By contrast, zebrafish shocked (sho) mutants have a defect in slc6a9, encoding GlyT1, a glycine transporter that is expressed by astroglial cells surrounding the glycinergic synapse in the hindbrain and spinal cord. GlyT1 mediates rapid uptake of glycine from the synaptic cleft, terminating synaptic transmission. In zebrafish sho mutants, there appears to be elevated extracellular glycine resulting in persistent inhibition of postsynaptic neurons and subsequent reduced motility, causing the ‘twitch once’ phenotype. We review current knowledge regarding zebrafish ‘accordion’ and ‘twitch once’ mutants, including beo and sho, and report the identification of a new α2 subunit that revises the phylogeny of zebrafish GlyRs.